Therapeutic Targeting of Type 2 Inflammation for the Treatment of Severe Asthma - C. Wu, Lawren; R. Arron, Joseph; M. Harris, Jeffrey; G. Matthews, John; Rosen, Karin (Clinical Anti-Inflammatory & Anti-Allergy Drugs (Discontinued), 2014)
Patients with severe asthma have disease that is poorly controlled despite use of standard combination therapies consisting of high doses of inhaled corticosteroids with other controller medications. Given the persisting disease and burden of morbidity for many of these patients, there remains a significant need for the development of new therapeutics to treat severe asthma. Preclinical studies have established a model of asthma pathogenesis that is driven by type 2 inflammation. Based on this paradigm, a number of therapeutic agents that target key features of type 2 inflammation, such as immunoglobulin E (IgE), mast cells, eosinophils, and type 2 inflammatory cytokines, have been generated and progressed into clinical development. Coupled with recent insights into the heterogeneity of asthma that have led to the development of diagnostic biomarkers to help select patients who may experience greater clinical benefit from these agents, several of these therapeutics have shown promising effects in clinical studies, with one therapeutic currently on the market. Here we review the results of clinical studies for these therapeutics and discuss how our understanding of asthma pathogenesis and disease heterogeneity may be leading to a new generation of therapies for severe asthma.
Keywords: eosinophil